Enhancing Motivation and Learning Outcomes in EFL Through the Cake Application: Evidence from a Quasi-Experimental Study - Nurul Susan Habawiyah; Ahmad Yani; Eny Enawaty; Venny Karolina; Urai Salam (FOSTER: Journal of English Language Teaching, 2026)
This study aims to analyze the effect of using the Cake application on students' motivation and learning outcomes in learning English. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The participants of this study consisted of 64 students divided into two groups: 32 students in the experimental class and 32 students in the control class. Data were collected through a learning motivation questionnaire and learning outcome tests administered before and after the treatment. The research instruments were first tested for validity using Pearson Product Moment correlation and for reliability using Cronbach's Alpha coefficient. Data analysis was conducted using normality tests, paired sample t-tests, independent sample t-tests, N-Gain analysis, and effect size calculation. The results of the study indicate that the use of the Cake application has a positive effect on students' motivation and learning outcomes. The improvement in motivation and learning outcomes in the experimental class tends to be higher than that in the control class, which used conventional learning methods. Furthermore, the N-Gain analysis shows that the improvement in the experimental class falls into the moderate category, while the control class falls into the low category. The effect size calculation also indicates that the use of the Cake application provides a moderate effect on improving students' motivation and learning outcomes. In conclusion, the Cake application can be used as an effective technology-based learning medium to enhance students' motivation and learning outcomes in English learning.